2002
DOI: 10.1291/hypres.25.329
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of a Long-Acting Angiotensin Converting Enzyme Inhibitor (Temocapril) and a Long-Acting Calcium Antagonist (Amlodipine) on Ventricular Ectopic Beats in Older Hypertensive Patients.

Abstract: We studied differences in the effects of a long-acting angiotensin-converting enzyme (ACE) inhibitor (temocapril) and a long-acting calcium channel blocker (amlodipine) on ventricular ectopic beats (VEB) in relation to sympathetic nerve activity in 46 patients with essential hypertension. We performed 24-h Holter electrocardiography and ambulatory blood pressure (BP) monitoring simultaneously, and examined blood samples during the baseline, temocapril and amlodipine treatment periods. The ambulatory BP was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…These results support those of our present study. SBP/DBP reductions were greater in the two prior studies (37,38) that observed pretreatment hypertensive patients than in the present study. The present study contributed the new finding that amlodipine treatment temporarily increased PR between baseline and 2 weeks.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…These results support those of our present study. SBP/DBP reductions were greater in the two prior studies (37,38) that observed pretreatment hypertensive patients than in the present study. The present study contributed the new finding that amlodipine treatment temporarily increased PR between baseline and 2 weeks.…”
Section: Discussioncontrasting
confidence: 81%
“…In our previous study (37) we observed 46 hypertensive patients (mean age: 68 years; baseline SBP/DBP: 168/92 mmHg). In that study, the mean clinic SBP and DBP were reduced to 29 and 10 mmHg at 4 to 8 weeks of amlodipine treatment, and PR in the higher-dose group (8.6 mg mean) increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The pulse rate during 24-h monitoring may reflect the diurnal condition of the patient more accurately than the office pulse rate. Mengden et al and Eguchi et al reported that the pulse rate increased significantly after amlodipine treatment in patients with hypertension (26,27), but the pulse rate was unchanged in many clinical trials with amlodipine (28,29). In the present study, differences in the baseline 24-h blood pressure values be- Other clinical studies of azelnidipine have also demonstrated that this drug does not increase the pulse rate (30,31).…”
Section: Discussionsupporting
confidence: 46%
“…We identified 11 eligible trials, including 6 trials conducted in China [11][12][13][14][15][16] and 5 in Japan; 17-21 2 had a cross-over design 17,20 and 9 had a parallel group design. [11][12][13][14][15][16]18,19,21 Characteristics of these trials are shown in Table 2.…”
Section: Efficacy In Lowering Ambulatory Blood Pressurementioning
confidence: 99%
“…The minimum luminal diameter of the coronary artery in all measured segments decreased significantly from baseline in the ACE Figure 1 Relation between the mean reduction and baseline level of daytime and nighttime systolic blood pressure by randomization group. The analysis included 10 calcium channel blocker (CCB) groups and 9 control groups from 9 trials, [11][12][13][14][15][16][17][18][19] respectively. Two trials were excluded, because daytime and nighttime blood pressures were not reported.…”
Section: Protection Against Target Organ Damagementioning
confidence: 99%